Ungkapan Istilah ‘Mas-Mas Jawa’ sebagai Representasi Budaya Jawa dalam Media Sosial Tiktok - RR. Balqis Alyamayadita Rahman (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2023)
Abstract The use of linguistic forms which are influenced by the speaker's thoughts can be explained through the meaning process, one of which is the expression of the term